Defining suitable reference genes for RT-qPCR analysis on human sertoli cells after 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure - Ribeiro, Mariana Antunes [UNESP]; Reis, Mariana Bisarro dos [UNESP]; Moraes, Leonardo Nazario de [UNESP]; Briton-Jones, Christine; Rainho, Claudia Aparecida [UNESP]; Scarano, Wellerson Rodrigo [UNESP] (Springer, 2014)
Quantitative real-time RT-PCR (qPCR) has proven to be a valuable molecular technique to quantify gene expression. There are few studies in the literature that describe suitable reference genes to normalize gene expression data. Studies of transcriptionally disruptive toxins, like tetrachlorodibenzo-p-dioxin (TCDD), require careful consideration of reference genes. The present study was designed to validate potential reference genes in human Sertoli cells after exposure to TCDD. 32 candidate reference genes were analyzed to determine their applicability. geNorm and NormFinder softwares were used to obtain an estimation of the expression stability of the 32 genes and to identify the most suitable genes for qPCR data normalization.
Keywords: TCDD; Human Sertoli cells; Reference genes; qPCR